PENGARUH KOMBINASI DOSIS PUPUK KANDANG AYAM DAN NPK (16:16:16) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNCIS (Phaseolus vulgaris L.) VARIETAS LOGAWA - Murti, Dian; Sumarti, Lily; Setiko, Putro Hairutomo; Erfan; Utami, Indri (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2023)
This study aims to determine the effect of a combination of dosage of chicken manure and NPK (16-16-16) on the growth and yield of chickpea plants (Phaseolus vulgaris L.) Varieties of Logawa. The research was carried out in Pangkalan Village, Cipinang Village, Cimaung District, Bandung Regency, West Java Province with an altitude of ±700 m above sea level, with C3 rainfall according to oldeman (1975). This research was conducted from July to September 2021. The research method used was a Randomized Group Design (RGD) consisting of 6 treatments and 4 tests. of treatment carried out in this study was A (0 tons/ha of Chicken Manure +0 kg/ha NPK), B (5 tons/ha of Chicken Manure+400 kg/ha of NPK), C (7.5 tons/ha of Chicken Manure+350 kg/ha of NPK), D (10 tons/ha of Chicken Manure+300 kg/ha of NPK), E (12.5 tons/ha of Chicken Manure+250 kg/ha of NPK) and F (10 tons/ha of Chicken Manure+300 kg/ha of NPK). The results showed that the administration of a combination of doses of 10 tons / ha of chicken manure and 300 kg / ha of NPK fertilizer (16; 16: 16) had a better influence on plant height, number of planting pods, and planting pod weight, giving a better influence on logawa variety chickpea plants. Keywords: Chickpeas, Chicken Manure, NPK (16:16:16).